Optimalisasi Perancangan Jaringan 4G LTE Pada Frekuensi 2300 MHZ Berbasis TDD Di Kabupaten Rokan Hulu - Muhammad Gunawan; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Long Term Evolution (LTE) is a technology developed by 3GPP as a development for cellular communication technology. LTE is a technology that can send and receive data at high speed. In Rokan Hulu Regency there are several areas that have not been reached by LTE and have a low Reference Signal Receipt Power (RSRP) value of approximately -100 dBm from ≥ -95 dBm from the standard. This study aims to optimize the LTE network based on planning by coverage and planning by capacity using the TDD radio access method. Specified frequency LTE is 2300 MHz, it is using 5 MHz and 10 MHz bandwidth. Coverage based on signal levels with a frequency of 2300 MHz with non-contoured maps at 5 MHz and 10 MHz bandwidth has a signal level value of ≥ -95 dBm at 99.99% and 100%. Coverage of signal level simulation results with contoured maps at 5 MHz and 10 MHz bandwidth has a signal level value of ≥ -95 dBm at 71.2% and 76.43%. So based on these parameters it can be concluded that the TDD technique with a bandwidth of 10 MHz is feasible to apply to Rokan Hulu Regency.Keywords: LTE, planning by coverage, planning by capacity, TDD, bandwitdh, signal level.